E-Recreational Hub: student gaming recreational area and Virtual Reality simulation chair with self-sustaining energy approach / Nur Farah Najwa Zulkiflee ... [et al.] - Zulkiflee, Nur Farah Najwa; Shahbudin, Mohammad Syathir Amini; Muhammad Fadzli, Fatin Nursyafiqah (2024)
The E-Recreational Hub (ERH) integrates gaming and Virtual Reality (VR) with sustainable design, catering to the growing demand among students for recreational and educational activities. Studies indicate significant engagement in sports, e-sports, and online gaming among Malaysians, underscoring the ERH’s relevance. ERH features 3D simulation chairs, an internet router, and a self-sustain electric supply powered by solar energy that align with SDG 13: Climate Action. ERH also enhances social interaction and global exploration while aligning with SDG 4: Quality Education. Equipped with high-speed 5G internet, power sockets, an online payment control system, and speakers, the hub provides an eco-friendly environment using reclaimed timber construction. The ergonomic design of simulation chairs ensures comfort and proper posture for the user. By offering a balanced natural setting and promoting sustainability, the ERH fosters a healthy mind and body. Its commercial potential is significant, appealing to environmentally conscious consumers and providing unique, high-tech facilities for gaming and learning. Future expansions could include additional technological features, educational tools, and food business opportunities, enhancing the ERH’s appeal and functionality.